2004
DOI: 10.1007/s00253-004-1588-4
|View full text |Cite
|
Sign up to set email alerts
|

Parameters and mechanistic studies on the oxidative ring cleavage of synthetic heterocyclic naphthoquinones by Streptomyces strains

Abstract: Screening of fungal and bacterial strains allowed selection of two Streptomyces strains ( S. platensis and S. cinnamonensis) that oxidatively cleave, in moderate to high yields (up to 65% in 24 h), the quinonic ring of a thiazole fused 1,4-naphthoquinone compound, INO5042, used as a model compound for a series of homologous substituted heterocyclic naphthoquinones. The respective products of these whole-cell biotransformations were identified as isomeric phenol-carboxylic acids resulting from a C-C bond cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that the derivatives of anthraquinones exert a number of biological effects including anticancer [23, 24], hepatoprotective [25], antimicrobial [26], and anti-inflammatory features [27]. Even though numerous biological activities of CA have been reported, there is only limited evidence for its effect on BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the derivatives of anthraquinones exert a number of biological effects including anticancer [23, 24], hepatoprotective [25], antimicrobial [26], and anti-inflammatory features [27]. Even though numerous biological activities of CA have been reported, there is only limited evidence for its effect on BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Previous pharmaceutical studies have shown that derivatives of anthraquinones exert multiple biological effects, including anticancer [37, 38], hepatoprotection [39], and antimicrobials [40]. A number of studies have also implied that extracts [41–43] containing CHR have a wide range of pharmacological activities, including anti-inflammation, antidyslipidemia, and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various other types of phytochemicals were isolated from SC, including anthraquinones, steroids, and flavones (Jang et al, 2007). These phytochemicals exerted a number of biological and pharmacological activities, including antimutagenic (Zhang and Yu, 2003), antihepatotoxic (Arosio et al, 2000) and antimicrobial effects (Fosse et al, 2004). However, the effects of these ingredients on MI/R injury in diabetic animals remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%